2016
DOI: 10.1128/mcb.00842-15
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Directly Binds to and Activates the Yeast AP-1-Like Transcription Factor Yap8

Abstract: cThe AP-1-like transcription factor Yap8 is critical for arsenic tolerance in the yeast Saccharomyces cerevisiae. However, the mechanism by which Yap8 senses the presence of arsenic and activates transcription of detoxification genes is unknown. Here we demonstrate that Yap8 directly binds to trivalent arsenite [As(III)] in vitro and in vivo and that approximately one As(III) molecule is bound per molecule of Yap8. As(III) is coordinated by three sulfur atoms in purified Yap8, and our genetic and biochemical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…ScYap5 is responsible for the activation of the high iron stress response (Li et al, 2008 ; Pimentel et al, 2012 ). ScYap7, the ohnolog of ScYap5, was recently found to be a repressor of the nitric oxide oxidase encoding gene YHB1 (Merhej et al, 2015 ) and ScYap8 is involved in the response to arsenic (Bobrowicz et al, 1997 ; Amaral et al, 2013 ; Kumar et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…ScYap5 is responsible for the activation of the high iron stress response (Li et al, 2008 ; Pimentel et al, 2012 ). ScYap7, the ohnolog of ScYap5, was recently found to be a repressor of the nitric oxide oxidase encoding gene YHB1 (Merhej et al, 2015 ) and ScYap8 is involved in the response to arsenic (Bobrowicz et al, 1997 ; Amaral et al, 2013 ; Kumar et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we confirmed that Arg7, Gly10 and Arg11 facilitate Yap8 high affinity binding to the Y8RE motif ( Figure 5C Our data show that Asn20 adjacent to the basic region is critical for high affinity binding of Yap8 to the 13 bp long Y8RE motif. The model suggests that Asn20 is not in direct contact with DNA, but influences the conformational space of the N-terminal tails (region [9][10][11][12][13][14][15][16][17][18][19]. The MD simulations of N20A Yap8 mutant-DNA complex showed that the mutant exhibits less stable contacts between the N-terminal and DNA, which could influence the overall stability of Yap8-DNA complexation.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of the Pap1 bZIP domain bound to the 8 bp YRE revealed that five amino acid residues of the basic region make direct contacts with a TTAC half-site, and these residues constitute the signature DNA recognition NxxAQxxFR sequence (2). This motif is highly conserved among members of the Pap1 subfamily suggesting that Yap proteins share a common mechanism of DNA binding (Figure 1 Yap8 sense the presence of these agents and coordinate activation of gene expression required for alleviation of metalloid toxicity (7)(8)(9)(10). Yap1 stimulates transcription of a large set of genes encoding proteins that are involved in adaptation to arsenic-induced oxidative stress and metalloid detoxification (7,9,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Besides TATA boxes and transcriptional start regions, MT gene promoters can have different motifs related to their expression induction, such as; metal responsive elements (MREs), antioxidant responsive elements (AREs), and glucocorticoid responsive elements (GREs) ( Gunther et al, 2012 ). Moreover, other binding-sites have been detected in some MT gene promoters, as GATA factors binding-sites ([A/T]GATA[A/G]) described in MTs from the nematode Caenorhabditis elegans ( Moilanen et al, 1999 ), AP-1 ( A ctivating P rotein-1 ) sites (TGA[G/C]TCA) and the GC boxes (GGGGCGGGG) related to the binding of bZIP ( b asic region leucine zip per ) TFs ( Shaulian and Karin, 2002 ; Haq et al, 2003 ; Jenny et al, 2006 ; Gutierrez et al, 2011 ; Kumar et al, 2015 ). A MTCM1 motif ( M e t allothionein C onserved M otif 1 ) has been described in the promoters of several MT genes from the ciliate Tetrahymena thermophila : MTT1 gene promoter has 6 MTCM1 motifs, MTT3 only has 2 motifs and MTT5 has 13 MTCM1 motifs in its duplicated promoter region ( Diaz et al, 2007 ; Gutierrez et al, 2011 ; de Francisco et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are also involved in gene expression regulation processes in response to different stimulus: cytokines, growth factors, viral or bacterial infections and stress conditions ( Durchdewald et al, 2009 ). Likewise, AP-1 has been related to MT gene expression increasing levels under different stress conditions in different organisms, such as; Saccharomyces cerevisiae ( Wu et al, 1993 ; Kumar et al, 2015 ), Crassostrea virginica ( Jenny et al, 2006 ), Drosophila melanogaster ( Kockel et al, 2001 ), and C. elegans ( Moilanen et al, 1999 ). An increase of MT-1 metallothionein gene expression level has been related to a higher gene expression of a gene encoding an AP-1 TF in mammalian cells after treatment with an oxidative stressor ( Braithwaite et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%